Influence of age and sex on the relative biological effectiveness of 13-keV/μm carbon ions for lifespan shortening of B6C3F1 Mice - Shizuko Kakinuma; Yi Shang; Yoshiko Amasaki; Shinobu Hirano-Sakairi; Tomoko Sawai; Takamitsu Morioka; Kazuhiro Daino; Benjamin J. Blyth; Mayumi Nishimura; Masaaki Sunaoshi; Chizuru Tsuruoka; Tatsuhiko Imaoka; et al. (PLoS ONE, 2025)
Epidemiological studies of Japanese atomic bomb survivors indicate that the risk of cancer from radiation exposure is higher in individuals who are relatively young at the time of exposure, with women facing a more significant risk compared to men. However, this type of data is limited for other radiation types, such as particle radiations. Low linear energy transfer (LET) carbon ions are a type of particle radiation to which humans may be exposed as cosmic radiation during long-duration space missions and as radiation passing through healthy tissue during carbon ion radiotherapy. This raises concerns about the risk of late complications, including cancer development. To address these issues, we examined the lifespan of mice after exposure to γ rays or low-LET carbon-ion beams, assessed the effects of sex and age at the time of exposure, and calculated the RBE. Male and female B6C3F1 mice of various ages (embryonic days 3, 13, and 17, and postnatal weeks 1, 3, 7, and 15) were whole-body irradiated a single time with 137Cs γ rays (662 keV) or 290-MeV/u monoenergetic carbon ions (LET, ~ 13 keV/µm), and their lifespan was analyzed. For both γ rays and carbon ions, the hazard ratio for mortality increased in a dose-dependent manner, was higher for females than for males, and peaked at 1 week of age at the time of exposure. The RBE of low-LET carbon ions for lifespan shortening was 0.9–1.8 for females and 1.2–2.0 for males, regardless of the age at exposure. Thus, the risk associated with low-LET carbon ion exposure varied with age and sex, but RBE did not. These findings provide essential data for assessing the impacts of low-LET carbon ion exposure.